Development of multimedia learning courseware for Arabic number / Noor Mashitah Khalid - Khalid, Noor Mashitah (2012)
Nowadays, Arabic is one of the famous languages learn by people in all over the world. Even in Malaysia, for the past few years, Arabic syllabus was implemented at primary school level. Each and every language has its own specialty. One of the specialties is number and it is vital to learn. In order to master Arabic number, we first have to get familiar with the pattern. This project paper will introduce the simplest way to remember, understand and apply few techniques that can help user. One of the techniques used is "Gitu-gitu". Many elements need to consider when design this courseware. The things are, the content of the courseware, screen design, button functioning and others. Thus, this courseware consists of animation, sound and pictures to encourage learning. The methodology used in this project is ADDIE method. It is composed of five phases which are analysis phase, design phase, development phase, implementation phase and evaluation phase. As a conclusion, this project had me its objectives even some constraints occurred. The constraints are it is difficult to make all users understand and poor in screen design. As a recommendation, it is advisable to use simple but understandable words and conduct a survey first before designing the prototype.